Mid‐life physical activity and late‐life cognitive performance among American Indians in the Strong Heart Study. (December 2021) - Carty, Cara L; Noonan, Carolyn; Muller, Clemma; Suchy‐Dicey, Astrid M; Fretts, Amanda M; Verney, Steven P; Howard, Barbara; Buchwald, Dedra
Abstract: Background: Research on factors associated with late‐life cognitive performance in diverse racial/ethnic groups is increasingly important due to the growing size and racial diversity of the elder population. American Indian elders suffer disproportionately from health conditions and behaviors that increase the risk of cognitive impairment, such as hypertension, diabetes, smoking, physical inactivity, and obesity. To inform prevention efforts in the growing at‐risk population, a better understanding of the relationships between modifiable cognitive risk factors and cognitive impairment is critical. Method: Using data on 816 American Indians from the Strong Heart Study, we measured associations between mid‐life physical activity (PA), assessed by questionnaire, and performance on 4 cognitive tests administered ∼21 years later. Cognitive tests assessed general cognitive function, phonemic fluency, verbal learning and memory and processing speed domains. To estimate associations, we used regression models with and without inverse probability weights that accounted for potential attrition bias due to drop out between the PA and cognitive assessments. A subset of participants (n=165) had pedometer PA measured ∼12 years after the questionnaire PA assessment. In separate models, we also estimated associations between average daily steps and cognitive test scores. Result: Participants had mean ages of 52 years at the questionnaire‐based PA assessment and 73 years at cognitive testing. The pedometer subset was mostly sedentary at the time of measurement with 66% completing <5000 steps/day, on average. Nevertheless, both questionnaire and pedometer measures of PA were positively associated with cognitive performance in later life. Participants in the top quartile of questionnaire‐based PA had Modified Mini‐Mental State examination scores 3.2 (95%CI: 1.5‐4.9) points higher than participants in the lowest quartile. Phonemic fluency scores also trended higher for participants in the top compared to bottom quantiles for both PA measures. We observed no associations between PA and tests assessing verbal learning and memory, or processing speed. Weighted model results were similar to unweighted results, but less precise. Conclusion: In this cohort of American Indians with relatively low levels of PA, positive associations between mid‐life PA and late‐life cognitive performance were domain‐specific and of modest clinical significance.